2008
DOI: 10.1097/mlg.0b013e31816d726c
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Efficacy of Newborn Hearing Screening: Strengths and Weaknesses (Success or Failure?)

Abstract: Derived from the present study: 1) repeated testing of "failed" newborns in the maternity hospital and before discharge leads to an acceptable referral rate of 2%; 2) the 1-month follow-up of "failed" newborns further limits the false positive results but leads to high rate of newborns lost to follow-up; 3) a dedicated secretariat system should be implemented to follow-up each "failed" newborn and remind parents about their follow-up appointments; and 4) additional measures such as detailed educational materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 18 publications
3
64
0
10
Order By: Relevance
“…For example, phenylketonuria (PKU), an autosomal recessive genetic disorder characterized by a deficiency in the enzyme hepatic phenylalanine hydroxylase occurs approximately once in every 14,000 births [2]. Therefore, early identification of hearing impairment is of paramount importance [5]. When early identification and intervention occurs, hearing-impaired children are likely to make dramatic progress, be more successful in school, and become more productive in their future social life [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, phenylketonuria (PKU), an autosomal recessive genetic disorder characterized by a deficiency in the enzyme hepatic phenylalanine hydroxylase occurs approximately once in every 14,000 births [2]. Therefore, early identification of hearing impairment is of paramount importance [5]. When early identification and intervention occurs, hearing-impaired children are likely to make dramatic progress, be more successful in school, and become more productive in their future social life [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early identification of hearing impairment is of paramount importance [5]. When early identification and intervention occurs, hearing-impaired children are likely to make dramatic progress, be more successful in school, and become more productive in their future social life [5]. Yoshinaga Itano reported that by the 26th month of age, infants with hearing loss, which were identified before the age of 6 months, had better mean scores in expressive language and receptive language in comparison with those identified after the age of 6 months [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Joint Committee on Infant Hearing, it is stated that these protocols give very good results (42). Newborns with hearing loss should be recognized by performing hearing screening for newborns and it is important to ensure the normal development by directing them to early treatment, to appropriate amplification or cochlear implantation if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Genel olarak yenidoğan işitme taramasında kalma oranı ise % 2-7 arasında verilmektedir. [21][22][23] Bizim çalışmamızda bu oran %0,9 olarak saptanmıştır. Bulgularımızın daha düşük olmasının nedeni yenidoğan işitme kaybı için yüksek risk faktörü olan gebelerin çalışma dışı bırakılması ve hastanemizde yenidoğan ünitesinin bulunmaması dolayısı ile önceden riskli olduğu tespit edilen gebelerin başka merkezlerde doğum yapması olabilir.…”
Section: Oae Tarama Testi Yaklaşık Olarak 4-8 Dakika Sürdü Bebekleriunclassified